The murder show - Goldman, Matt, 1962- (Forge, Tor Publishing Group, 2025)
Showrunner Ethan Harris had a hit with The Murder Show, a television crime drama that features a private detective who solves cases the police can't. But after his pitch for the fourth season is rejected by the network, he returns home to Minnesota looking for inspiration. His timing is fortunate - his former classmate Ro Greeman is now a local police officer, and she's uncovered new information about the devastating hit and run that killed their mutual friend Ricky the summer after high school. She asks Ethan to help her investigate and thinks that if he portrays the killing on The Murder Show, the publicity may bring Ricky's killer to justice. Ethan is skeptical that Ricky's death was anything but a horrible accident, but with the clock running out on his career, he's willing to try anything. It doesn't take long for them to realize they've dug up more than they bargained for. Someone is dead set on stopping Ethan and Ro from looking too closely into Ricky's death - even if keeping them quiet means killing again...